Fluoride concentration in saliva and biofilm fluid following the application of three fluoride varnishes. (May 2017) - Al Dehailan, L.; Lippert, F.; González-Cabezas, C.; Eckert, G.J.; Martinez-Mier, E.A.
Abstract: Objective: Most of the commercially available fluoride varnishes (FV) have not been evaluated for their cariostatic properties. Consequently, the aim of this in vivo study was to investigate intra-oral fluoride retention and clearance patterns from three different FV. Methods: Eighteen subjects (7–11 years) participated in a laboratory analyst-blinded, randomized, crossover study comparing the ability of 5% sodium fluoride varnishes (CavityShield-CS, Enamel Pro-EP, Vanish-V) to enhance fluoride concentrations in biofilm fluid, centrifuged and whole saliva over a period of 48 h after a single FV application. Results: Similar fluoride concentration × time patterns were noted for all investigated FV and studied variables, with the highest fluoride concentrations observed for the first biological sample collected after FV application (30 min). Mean ± SE (area under fluoride clearance curve) values were (μg F/g or ml × min): biofilm fluid − CS (472 ± 191), EP (423 ± 75),  V (1264 ± 279); centrifuged saliva − CS (42 ± 7), EP (19 ± 3),  V (41 ± 8); whole saliva − CS (68 ± 11), EP (64 ± 10),  V (60 ± 7). V delivered more fluoride to biofilm fluid than CS (p = 0.0116) and EP (p = 0.0065), which did not differ (p = 0.27). For centrifuged saliva, CS and V were not significantly different (p = 0.86), but resulted in higher fluoride retention than EP (p < 0.0008). No significant differences among FV were observed for whole saliva (p = 0.79). Conclusion: The present study has shown that FV vary in their ability to deliver fluoride intra-orally potentially related to formulation differences. To what extent the present findings relate to clinical efficacy remains, however, to be determined. Clinical significance: Clinical research that investigates fluoride release patterns into saliva and biofilm fluid from different FV products is insufficient. More research is needed to investigate different FV formulations for their efficacy in order to help clinicians make better evidence based treatment choices.